Factors Related to Complete Basic Immunization of Infants during Covid-19 Pandemic at Gunung Kaler Public Health Center, Tangerang District in 2021 - Nurul Husnul Lail; Yayuk Hartati; Triana Indrayani (Universitas STRADA Indonesia, 2021)
This research was conducted aiming to determine the factors associated with giving complete basic immunization to infants during Covid-19 pandemic at Gunung Kaler Public Health Center, Tangerang District in 2021. This research was a descriptive correlation study using purposive sampling method. The sampling further obtained 91 mothers who had babies at the age of 9-12 months old. The research instrument used was a questionnaire, while the statistical test used was chi-square. The results of this study indicated that there was a relationship between knowledge, attitudes, beliefs, sources of information, and health care support with providing complete basic immunization to infants during Covid-19 pandemic at Gunung Kaler Public Health Center, Tangerang District in 2021. It was found that 60.4% of children at the age of 9-12 months old did not receive complete basic immunization during Covid-19 pandemic at the Gunung Kaler Health Center, Tangerang District.